Efektivitas Layanan Konseling Individual Pendekatan Rebt Untuk Mengunrangi Kecemasan Berbicara Di Depan Umum Pada Peserta Didik di SMA Negeri 2 Palangkaraya: The Effectiveness Of The Individual Rebt Approach To Services To Reduce Anxiety Speaking In General Ahead In Students In Palangkaraya 2 State High - Fitriani Fitriani; Esty Aryani Safithry (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to: (1) determine the anxiety profile of class X students in Palangkaraya 2 High School, (2) to find out the effectiveness of individual counselling with the REBT approach to reduce anxiety in speaking students in Palangkaraya 2 High School. The study population was all students of class X MIPA 4 Palangkaraya 2 Public High School as many as 42 students and who were surveyed as a sample of research or population of 2 students. Data collection techniques using observation, questionnaires and interviews. The method used is quantitative experiments, data analysis techniques using the t-test formula (paired sample t-test)